The genetic controlled hydroxylation pattern of the anthocyanin b-ring in Silene dioica is not determined at the p-coumaric acid stage - Heinsbroek, R.; Brederode, J. van (Elsevier, 1980)
The basic C-15 skeleton of flavonoids is formed by the head-to-tail condensation of three malonyl-CoA units to one molecule of hydroxycinnamoyl-CoA. The A-ring and part of the heterocyclic ring are derived from the acetate units, the B-ring from the hydroxycinnamoyl ester. The basic C-15 flavonoid is then further modified to yield the various flavonoid classes. In this biosynthetic pathway, the hydroxylation pattern of the B-ring can either be determined at the C-9 level, by starting with the appropriate hydroxycinnamoyl-CoA ester, or at the C-15 level, by hydroxylation of one of the C-15 intermediates. In Silene dioica the hydroxylation pattern of the B-ring of the anthocyanidin molecule, and of the acyl group bound to the terminal sugar at the 3-position, is controlled by gene P, whereas the binding of the acyl group is governed by gene Ac. The hydroxylation pattern of the acyl group, however, corresponds with that of the B-ring of the anthocyanidin molecule. Thus in p/p Ac/Ac plants, in which only pelargonidin glycosides are found, the acyl group is p-coumaric acid. In P/P Ac/Ac plants the anthocyanidin is cyanidin, and the acyl group is caffeic acid. This suggests that homozygous recessive p/p plants are unable to synthesize caffeic acid, which is used both as a precursor in the biosynthesis of the anthocyanidin molecule and for acylation. In this paper, we have investigated whether gene P is involved in the conversion of p-coumaric to caffeic acid.
Keywords: Biologie; Silene dioica; Caryophyllaceae; red campion; anthocyanin biosynthesis; hydroxylation; genetic control; p-coumaric acid; caffeic acid; Silene dioica; Caryophyllaceae; red campion; anthocyanin biosynthesis; hydroxylation; genetic control; p-coumaric acid; caffeic acid